Light- and transmission-electron-microscopic investigations on distribution of CD44, connexin 43 and actin cytoskeleton during the foreign body reaction to a nanoparticular hydroxyapatite in mini-pigs - Wenisch, Sabine; Cavalcanti-Adam, Elisabetta A. (Acta biomaterialia, 2012)
Foreign body giant cells (FBGCs) are formed by fusion of mononucleated macrophages during the foreign body response to a nanoparticulate hydroxyapatite (HA) implanted in defects of mini-pig femura. The molecular mechanisms underlying the formation of FBGCs are still largely obscure. Here we propose connexin 43 (cx43) and CD44 as candidate molecules involved in the fusion process. Immunohistochemistry and ultrastructural immunogold labeling indicated that cx43 is present within the ruffled border of FBGCs and is the main component of gap junctions formed between fusing macrophages. CD44 was strongly expressed during clustering and fusion of mononucleated macrophages. FBGCs adhering apically at the implanted HA showed CD44 reactivity only along the basolateral aspects of the plasma membranes, while podosome formation was observed within the sealing zone and ruffled border. Taken together, these findings demonstrate that cx43 and CD44 are part of the fusion machinery responsible for the formation of FBGCs. Furthermore, the results of microfilament and cx43 labeling suggest a functional role for podosomes and hemi-channels in biomaterial degradation.